Strategi Hubungan Masyarakat Dalam Upaya Meningkatkan Penerimaan Siswa Baru Di Sma Muhammadiyah 5 Yogyakarta - Habibah, Alifia Fifi; Mahmudah, Fitri Nur (Edugama: Jurnal Kependidikan dan Sosial Keagamaan, 2022)
Public relations which is abbreviated as "public relations" is also one of the important managements in educational institutions. Once the importance of public relations, every institution, especially educational institutions, always has a deputy principal who is specifically tasked with managing public relations, especially for an Islamic educational institution. In D.I Yogyakarta, many private schools have been established by prioritizing religious learning. One of them is the Muhammadiyah Foundation school. The research that the author will do with previous research is that researchers will examine public relations strategies in an effort to increase new student admissions at SMA Muhammadiyah 5 Yogyakarta. The success of the Public Relations strategy in an effort to increase new student admissions at SMA Muhammadiyah 5 Yogyakarta can be measured by the number of new students enrolling in the school. based on research that has been carried out by researchers, it can be concluded that: 1) The quality of student selection in the public relations strategy as an effort to increase new student admissions needs to be carried out starting from program planning, organizing or forming a PPDB team. 2) Improvement or improvement of all aspects of communication and service is a must in the implementation of a good public relations strategy. 3) A good promotion strategy must also be applied in an effort to increase new students by using print media and social media effectively and efficiently